Deviated nose. Open or closed rhinoplasty? - Gonçalves Ferreira, Miguel (2008)
Various ana tomical deformations of the nose may give it a crookedappearance. The concept of "Deviated Nose " has multiple synonyms but in most cases it refers always to a deviated pyramid in the sagital plane. The deformity can be congenital or acquired, most frequently traumatic. The correction of this group of deformities is one of the biggest challenge for the Surgeon . The principie of correction can be either to "camouflage" the defect or to realign and reconstruct the symmetric anatomy or combine both principies. ln this article, various surgical strategies will be discussed with emphasis on the external or "open" approach.